2004
DOI: 10.1158/0008-5472.can-03-0974
|View full text |Cite
|
Sign up to set email alerts
|

The Drug Salicylamide Is an Antagonist of the Aryl Hydrocarbon Receptor That Inhibits Signal Transduction Induced by 2,3,7,8-Tetrachlorodibenzo- p -dioxin

Abstract: ABSTRACT2,3,7,8-Tetrachlorodibenzo-p-dioxin (TCDD) is a widespread environmental contaminant, that has been linked with a variety of deleterious effects on human health, including increased cancer rates and reproductive anomalies. The detrimental effects of TCDD are mediated via the aryl hydrocarbon receptor (AhR), a transcription factor that regulates the expression of the carcinogen-activating enzymes cytochromes P-450 (CYP) 1A1, 1A2, and 1B1. In the present study, we examined the ability of synthetic deriva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 43 publications
5
49
0
Order By: Relevance
“…Another possible cause is that SFN can compete with TCDD in binding to AhR-heat shock protein 90 dimer. Consequently, the signal transduction leading to the expression of CYP1A1 is blocked (Henry et al, 1999;MacDonald et al, 2004). In present study, the results of molecular docking also revealed that SFN can bind to AhR and CYP1A1 by hydrogen bonds, respectively (Fig.…”
Section: Discussionsupporting
confidence: 62%
“…Another possible cause is that SFN can compete with TCDD in binding to AhR-heat shock protein 90 dimer. Consequently, the signal transduction leading to the expression of CYP1A1 is blocked (Henry et al, 1999;MacDonald et al, 2004). In present study, the results of molecular docking also revealed that SFN can bind to AhR and CYP1A1 by hydrogen bonds, respectively (Fig.…”
Section: Discussionsupporting
confidence: 62%
“…CTNNA1 has been shown to be downregulated in human squamous cell carcinoma of the oesophagus [15,27], our microarray data showed upregulation of the gene while the qRT-PCR showed a downregulation in 11E6 and further downregulation in 18E6 compared to mock which suggest that 18E6 might be more potent in inhibiting the CTNNA1 expression than 11E6. CYP1B1 is a metabolic enzyme involved in degradation of environmental carcinogens like benzo(a)-pyrene and other polycyclic hydrocarbons (PAHs) present in environmental pollution and cigarette smoke which forms DNA adducts [22], and converts them to soluble products which are excreted out. Elevated CYP1B1 expression may result in a greater load of reactive oxygen intermediates (ROMs) causing genotoxic stress and tumour initiation [12,37].…”
Section: Transcription Regulationmentioning
confidence: 99%
“…Schild assay has previously been used to demonstrated that PCB 128 is a competitive antagonist of the fish AhR (Hestermann et al, 2000). It is apparent that several AhR ligands exhibit both agonistic and antagonistic activities ) (MacDonald et al, 2004) (de Medina et al, 2005, and classical receptor theory predicts that partial agonists will cause different levels of response, dependent upon receptor number and receptor-coupling (Kenakin, 1997); indeed, cell-specific response to partial agonists of AhR has been demonstrated (Zhang et al, 2003). The relative quantification of these activities is essential for understanding how AhR receptor number and coupling are related to the physiological and toxicological consequences of exposure to AhR ligands.…”
Section: /2/09 Page 13mentioning
confidence: 99%